Temporal bone measurements on high-resolution computed tomography - BALTACIOĞLU, FEYYAZ (B C DECKER INC, 2004)
The distances between the important neural and vascular structures in normal temporal bones were measured by using high-resolution computed tomography (HRCT). We examined 100 normal ears in 50 subjects ranging in age from 15 to 72 years (mean age 39 years). We measured the distances from the medial lip of the posterior wall of the internal auditory canal to the medial wall of the vestibule (mean 9.7 mm), from the cochlea to the tympanic segment of the facial canal (mean 1.76 mm), from the medial wall of the vestibule to the lateral aspect of the lateral semicircular canal (mean 8.03 mm), and from the external auditory canal to the lateral sinus (mean 13.2 mm). HRCT examination is the best method for defining the morphology of temporal bone.
Keywords: high-resolution computed tomography; temporal bone; MASTOID PNEUMATIZATION; 3-DIMENSIONAL CT; LATERAL SINUS; POSITION; ANATOMY